Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Pelayanan Aparatur Pemerintah Desa Yang Di Mediasi Oleh Efektivitas Kerja (Studi Pada Kecamatan Bumiaji) - Firda Dewi Saputri; M. Cholid Mawardi; Muhammad Sirojuddin Amin (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the effect of Work Motivation and Job Satisfaction on Apparatus Service with Work Effectiveness as a mediating variable among village government officials in Bumiaji District. This research uses a quantitative approach with a survey method through questionnaire distribution to respondents from village apparatus. The sampling technique used was purposive sampling. The data analysis method applied was Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results show that Work Motivation and Job Satisfaction have a significant effect on Apparatus Service. Job Satisfaction also has a significant effect on Work Effectiveness, while Work Motivation does not have a significant effect on Work Effectiveness. Work Effectiveness is proven to have a significant effect on Apparatus Service and is able to mediate the effect of Job Satisfaction on Apparatus Service, but does not mediate the effect of Work Motivation on Apparatus Service. These findings indicate that improving the quality of apparatus service is influenced not only by motivation and job satisfaction factors, but also by work effectiveness as a strengthening mechanism. This study is expected to contribute to the development of public sector human resource management and serve as a practical reference for village governments in improving service quality. Keywords: Work Motivation, Job Satisfaction, Work Effectiveness, Apparatus Service